ANALISIS YURIDIS PERALIHAN HAK TANAH MILIK ADAT DENGAN AKTA JUAL BELI YANG DIBUAT OLEH PPAT ( STUDI KABUPATEN ACEH BESAR ) - M. HEIKAL ARFIAN (PREMISE LAW JURNAL, 2016)
Ground in Aceh, particular Punie Village, District Darul Emirate Aceh Besar district that the land has not been that much certificate and no correspondence, but the land has been passed down from parents in advance without any letter. Basic description of that land in Aceh Besar district is customary land ownership is a Certificate issued by Keuchik (Village Head), which describes information about the history of the land as well as knowing the limits and known by the public. Transition customary land rights in Aceh Besar district uses Deed of Sale and Purchase made by and in front of the Land Deed Officer (PPAT), authorizing the legal acts of sale and purchase between the seller and the buyer. But in terms of the transition here, PPAT check and ask the seller if there is a certificate of Keuchik that the land is the land ownership rights of indigenous before making a purchase, the Land Office in this case the measurement was imported also re-measure the land, to ensure certainty broad, if a time will be registered rights. Keywords: Indigenous Land Property Rights, Land That Not Certificate,Deed Of Sale And Purchase, Land Deed Officer